Effect of DNDF and Macro Variables on Exchange Rate - Fiqi Tsaniyatus Sa'adah (Economics Development Analysis Journal, 2020)
The purpose of this study was to determine the effect of DNDF (Domestic Non Deliverable Forward) policy, interest rates, money supply and IHSG on the IDR/ USD exchange rate. This type of research uses a quantitative approach. The type of data used in this research is secondary data from 2014 to 2019. The variables used in this study are 4 variables with based on the theory of determining foreign currency. Data analysis method used Ordinary Least Square method with hypothesis testing t test and F test. The results of this study indicate that DNDF has a significant negative effect on the IDR / dollar exchange rate, while the IHSG has no significant negative effect on the IDR / dollar exchange rate. Conversely, interest rates and the money supply have a significant positive effect on the IDR / dollar exchange rate. Overall DNDF, interest rates, money supply and IHSG together influence the IDR / dollar exchange rate. Suggestions from this study are (1) business actors can participate in hedging the IDR which can maintain the stability of the exchange rate. (2) holders of monetary authorities intervene and be more careful in setting interest rates and need to be well coordinated. (3) holders of monetary authority can intervene by suppressing the money supply which will have an impact on depreciation. (4) Improving stock performance starts with competitive interest rates in Indonesia and several policy innovations in the derivative market such as DNDF policy.